Effect of head rotation on visualisation of carotid artery and jugular vein in ijv cannulation: an observational analytical study - Poonam Kalra; Gursevak Maan; Satveer Singh Gurjar; Deepak Choudhary (Creative Pharma Assent, 2023)
Background: The relationship between the common carotid artery (CCA) and the internal jugular vein (IJV) plays a crucial role in the process of internal jugular vein (IJV) cannulation, and this relationship often undergoes changes with head rotation. Methods: In this analytical, observational study, we aimed to compare the effect of 15-degree and 45-degree head rotation on the visualization of the IJV and CCA among 30 patients undergoing IJV cannulation for central venous access. Ultrasound guidance was used during the cannulation procedure. Results: Our findings revealed that greater overlapping of the IJV, specifically at the 12 o'clock position, was observed in cases with a 45-degree head rotation, whereas a lesser degree of overlapping (IJV at the 10 o'clock position) was observed with head in the neutral position. Conclusion: Based on our observations, we conclude that maintaining a head neutral position during IJV central line insertion under ultrasound guidance is safer compared to a 45-degree neck rotation. This information can contribute to improved safety and efficacy during IJV cannulation procedures.